2018
DOI: 10.1186/s13584-018-0221-4
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum reform: Why? What? How? and how will we know it works?

Abstract: In a recent IJHPR article, Dankner et al. describe a reform in one longitudinal strand within Basic Medical Education i.e.“ public health and preventive medicine curriculum” using a Competency Based Medical Education approach. This reform raises several concerns: What should prompt a medical school to change a curriculum? How should such change be conducted? What kinds of paradigms may inform such a change? What constitutes a success in a curricular reform? And, how can curricular reform be evaluated within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…In Israel, factors which influenced changes and developments in Chemistry curriculum included political, cultural socio-economic, and scientific, industrial and technological innovations. Similarly, Reis (2018) suggests that curriculum reform should follow a clear vision and mission, a selected educational paradigm, and pay attention to stakeholders, context, culture and politics.…”
Section: Introductionmentioning
confidence: 99%
“…In Israel, factors which influenced changes and developments in Chemistry curriculum included political, cultural socio-economic, and scientific, industrial and technological innovations. Similarly, Reis (2018) suggests that curriculum reform should follow a clear vision and mission, a selected educational paradigm, and pay attention to stakeholders, context, culture and politics.…”
Section: Introductionmentioning
confidence: 99%
“…Reform, particularly in an intricate system like a medical school, is full of problems such as resistance, power, inertia, and ego challenges which necessitate a planned method, as well [34].…”
Section: Resultsmentioning
confidence: 99%
“…A study in the United States reported that 98.5% of undergraduate students received quite poor health education communication (28). Findings from a study in England also pointed out the gap in public health and epidemiology training curriculum, and reformation to improve the training for medical students has been started (29). In the LMIC group, 86% of Pakistan medical students were not satisfied with the epidemiology approach at the university (30).…”
Section: Discussionmentioning
confidence: 99%